AI for games - Millington, Ian (CRC Press, Taylor & Francis Group, 2019)
AI is an integral part of every video game. This book helps professionals keep up with the constantly evolving technological advances in the fast growing game industry and equips students with up-to-date information they need to jumpstart their careers. This revised and updated Third Edition includes new techniques, algorithms, data structures and representations needed to create powerful AI in games. Key Features * A comprehensive professional tutorial and reference to implement true AI in games * Includes new exercises so readers can test their comprehension and understanding of the concepts and practices presented * Revised and updated to cover new techniques and advances in AI * Walks the reader through the entire game AI development process.